On hypersurfaces in a locally affine Riemannian Banach manifold II - El-Said R. Lashin; Tarek F. Mersal (International Journal of Mathematics and Mathematical Sciences)
In our previous work (2002), we proved that an essential second-order hypersurface in an infinite-dimensional locally affine Riemannian Banach manifold is a Riemannian manifold of constant nonzero curvature. In this note, we prove the converse, in other words, we prove that a hypersurface of constant nonzero Riemannian curvature in a locally affine (flat) semi-Riemannian Banach space is an essential hypersurface of second order.